In-vitro sperm mucus penetration test for fertility assessment in cows - BENNUR, P C; HONNAPPAGOL, S S; TANDLE, M K (The Indian Journal of Animal Reproduction, 2005)
The estrual cervico-vaginal mucus (CVM) samples were collected from 44 regularly cycling pleuriparous cows prior toartificial insemination and the same were subjected for in-vitro sperm mucus penetration tests like slide, polyethylene and capillarytube tests. Following the collection of CVM the animals were inseminated and screened for pregnancy after 60 days. Among the invitrosperm cervical mucus penetration tests, the slide and capillary tube tests were found to be of diagnostic value in assessing thefertility of cows.
Keywords: Cervico-vaginal mucus; in-vitro tests